Gastric Sarcoidosis: A Rare Clinical Presentation. (4th December 2013) - Tokala, Hemasri; Polsani, Karthik; Kalavakunta, Jagadeesh K.
Abstract : Gastrointestinal (GI) sarcoidosis is a very rare disease, which clinically presents along with systemic disease or as an isolated finding. Gastric sarcoidosis is the most common form of GI sarcoidosis. Symptomatic gastric sarcoidosis is rare and only few case reports have been described in the literature with well-documented histological evidence of noncaseating granulomas. We present an interesting case of gastric sarcoidosis in a 39-year-old Caucasian man with symptoms of epigastric pain and profound weight loss. His endoscopic gastric mucosal biopsies revealed noncaseating granulomas consistent with gastric sarcoidosis. Treatment with oral steroids alleviated his symptoms with no recurrence in 2 years. Gastric sarcoidosis should be considered in patients with history of sarcoidosis and GI symptoms.